The best cutoff value of middle cerebral artery peak systolic velocity for the diagnosis of fetal homozygous alpha thalassemia-1 disease - Fuanglada Tongprasert (2019)
© 2019 John Wiley & Sons, Ltd. Objective: To determine the best cutoff value of middle cerebral artery peak systolic velocity (MCA-PSV) for the diagnosis of fetuses with homozygous alpha thalassemia-1 disease. Methods: Pregnancies at risk for fetal homozygous alpha thalassemia-1 disease at 18 to 22 weeks were recruited. MCA-PSV was measured before cordocentesis for hemoglobin typing and complete blood count. The performance of the MCA-PSV for identifying affected fetuses was evaluated using a best cutoff value derived from the receiver operating characteristic (ROC) curve. Results: Among 142 fetuses at risk, 46 (32.4%) fetuses were diagnosed as affected by homozygous alpha thalassemia-1 disease and were categorized as mild anemia (16.3%), moderate anemia (58.1%), and severe anemia (25.6%). With the best cutoff point of MCA-PSV > 1.30 multiples of the median (MoM) or >30.0 cm/s, the sensitivity for predicting fetal homozygous alpha thalassemia-1 was 100%. Conclusions: MCA-PSV > 1.30 MoM is the best cutoff value for the diagnosis of all degrees of fetal anemia from homozygous alpha thalassemia-1 fetuses. Because of its simplicity for interpretation and high efficacy, a cutoff value of MCA-PSV > 30 cm/s can also be used as an alternative marker for fetal anemia screening during 18 to 22 weeks of gestation.